Combined deletion of Bap1, Nf2, and Cdkn2ab causes rapid onset of malignant mesothelioma in mice - Badhai, Jitendra; Pandey, Gaurav Kumar; Song, Ji-Ying; Krijgsman, Oscar; Bhaskaran, Rajith; Chandrasekaran, Gayathri; Kwon, Min-Chul; Bombardelli, Lorenzo; Monkhorst, Kim; Grasso, Cristoforo; Zevenhoven, John; van der Vliet, Jan; et al. (The Journal of experimental medicine, 2020)
We have generated mouse models of malignant mesothelioma (MM) based upon disruption of the Bap1, Nf2, and Cdkn2ab tumor suppressor loci in various combinations as also frequently observed in human MM. Inactivation of all three loci in the mesothelial lining of the thoracic cavity leads to a highly aggressive MM that recapitulates the histological features and gene expression profile observed in human patients. The tumors also show a similar inflammatory phenotype. Bap1 deletion alone does not cause MM but dramatically accelerates MM development when combined with Nf2 and Cdkn2ab (hereafter BNC) disruption. The accelerated tumor development is accompanied by increased Polycomb repression and EZH2-mediated redistribution of H3K27me3 toward promoter sites with concomitant activation of PI3K and MAPK pathways. Treatment of BNC tumor-bearing mice with cisplatin and pemetrexed, the current frontline treatment, prolongs survival. This makes the autochthonous mouse model described here very well suited to explore the pathogenesis of MM and validate new treatment regimens for MM, including immunotherapy.